AZD3293: Pharmacokinetic and Pharmacodynamic Effects in Healthy Subjects and Patients with Alzheimer's Disease - Cebers, Gvido; Alexander, Robert C; Haeberlein, Samantha Budd; Han, David; Goldwater, Ronald; Ereshefsky, Larry; Olsson, Tina; Ye, Naidong; Rosen, Laura; Russell, Muir; Maltby, Justine; Eketjäll, Susanna; et al. (Journal of Alzheimer's disease, 2017)
AZD3293 (LY3314814) is a promising new potentially disease-modifying BACE1 (β-secretase) inhibitor in Phase III clinical development for the treatment of Alzheimer's disease. Reported here are the first two Phase I studies: (1) a single ascending dose study evaluating doses of 1-750 mg with a food-effect component (n = 72), and (2) a 2-week multiple ascending dose study evaluating doses of 15 or 50 mg once daily (QD) or 70 mg once weekly (QW) in elderly subjects (Part 1, n = 31), and 15, 50, or 150 mg QD in patients with mild to moderate Alzheimer's disease (Part 2, n = 16). AZD3293 was generally well tolerated up to the highest doses given. No notable food effects were observed. PK following multiple doses (Part 2) were tmax of 1 to 3 h and mean t1/2 of 16 to 21 h across the 15 to 150 mg dose range. For single doses of ≥5 mg, a ≥70% reduction was observed in mean plasma Aβ40 and Aβ42 concentrations, with prolonged suppression for up to 3 weeks at the highest dose level studied. Following multiple doses, robust reductions in plasma (≥64% at 15 mg and ≥78% at ≥50 mg) and cerebrospinal fluid (≥51% at 15 mg and ≥76% at ≥50 mg) Aβ peptides were seen, including prolonged suppression even with a QW dosing regimen. AZD3293 is the only BACE1 inhibitor for which prolonged suppression of plasma Aβ with a QW dosing schedule has been reported. Two Phase III studies of AZD3293 (AMARANTH, NCT02245737; and DAYBREAK-ALZ, NCT02783573) are now ongoing.